Teori Belajar Humanistik Terhadap Motivasi Siswa Meningkatkan Prestasi Belajar - Setiadi, Wisnu Agus; Aryani, Dini; Fu’adin, Ahmad (CV. ITTC INDONESIA, 2023)
Humanistic learning theory is one of the most important theories in educational psychology. This theory emphasizes the importance of individual experiences and how these experiences affect the way individuals learn. The main goal of humanistic learning theory is to understand students' motivations and how these motivations affect their learning achievement. learning is not only about memorizing material but more than that learning is how someone is free to find their own way and can do it anywhere. As long as it brings good results for him. According to Humanistic theory, the purpose of learning is to humanize humans. The learning process is considered successful if students understand the environment and themselves. Students in the learning process must strive to be able to achieve self-actualization little by little.